Analysis of Korean Middle School Students’ Scientific Interpretation Differences With or Without Arrows in the Energy Pyramid - Kim, D. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
This study analyzed differences in Korean middle school students’ scientific interpretation of the energy pyramid diagram, which is a central concept of ecosystem learning, based on whether or not arrows were presented in the chart. Two classes that did not show statistically significant differences in school science academic achievement were selected. One class was shown the energy pyramid diagram with arrows, and the other without. A quasi-experimental design was adopted for quantitative research. The study found that the group interpreting the energy pyramid with arrows had a statistically significant scientific interpretation than the group interpreting the energy pyramid without arrows. In other words, arrows aided understanding of the concepts of size, biomass, and energy transfer of biological elements in the energy pyramid. In addition, the arrows aided understanding of the meaning of each piece of a pie chart, as the amount of biomass or energy being transferred to the next level of nutrition as pieces of a pie chart. Thus, it was concluded that the arrows in the energy pyramid were efficient visual elements in conveying the flow of matter and energy between living creatures. Based on the results, this study recommends that science textbooks should use arrows for more efficient understanding of scientific phenomena throughout textbooks beyond only the “ecosystem” topic.